Penggunaan Media Diorama dalam Mengatasi Kesulitan Siswa Kelas V Yayasan Al- Hidayah dalam Memahami Peran Pelaku Ekonomi - Julia Amelia Sormin; Anggili Pratama; Afrida Hanum Lubis; Sekar Melati Pasariu; Najwa Fadhilah Siregar; Nabila Olivia; Haya Sabila Aulia Br Munthe; Nakaya Hanaro Sihotang (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
This research was conducted to help fifth-grade students of the Al-Hidayah Foundation overcome difficulties in understanding the material on the role of economic actors through the use of diorama media. The background of the research departs from the students' low understanding of abstract concepts such as producers, consumers, and distributors, which have been taught using monotonous lecture methods. The research used a Classroom Action Research (CAR) approach with the Kemmis and McTaggart model which was implemented in several cycles. The results showed a significant increase in understanding after the use of diorama media. Before being implemented, only 13.3% of students were able to understand the role of economic actors, whereas after the use of diorama media, this number increased to 80%. Diorama media has been proven to be able to concretize abstract concepts, increase learning motivation, and strengthen students' understanding of economic activity material. Thus, diorama can be used as an alternative media for learning IPAS in elementary schools, especially on the topic of the role of economic actors.